Emotions as A Driving Factor of Political Conformity Among Generation Z in Regional Elections - Purwanto, Joko; Marlina (IJESS International Journal of Education and Social Science, 2025)
This study aims to analyze the influence of conformity on the emotional aspects of Generation Z in determining political choices in local elections. The research involved 40 respondents who are online game players in Gowa Regency, consisting of both male and female participants. The research instrument used questionnaires containing 32 items for the conformity variable and 32 items for the emotional variable. The descriptive analysis showed that the respondents’ conformity level was in the moderate category with a mean score of 37 (SD = 4.03), while their emotional level was also in the moderate category with a mean score of 37.01 (SD = 5.6). Normality and linearity tests confirmed that the data were normally distributed (p > 0.05) and revealed a significant linear relationship between the two variables (p = 0.02). Simple regression analysis indicated that conformity influenced the emotional aspects of Generation Z by 12.6%, with a regression coefficient of 0.415, suggesting a positive relationship. These findings highlight that the higher the tendency of Generation Z to conform to their group, the stronger the emotional influence in their political decision-making. The results are consistent with social psychology and emotional intelligence theories, which emphasize that social pressure can reinforce individuals’ emotional responses. Therefore, conformity plays a crucial role in understanding the dynamics of Generation Z’s emotional involvement, particularly in the context of political behavior in the digital era.